2018
DOI: 10.1002/chem.201803580
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing a Pyrazine‐Containing Aggregation‐Induced Emission Luminogen as an Efficient Photosensitizer for Imaging‐Guided Two‐Photon Photodynamic Therapy

Abstract: The development of novel photosensitizers with aggregation-induced emission (AIE) characteristics has aroused tremendous interest, because it could combine efficient bioimaging with precise photodynamic therapy, which would thus dramatically promote applications in biomedical treatment. Among various AIE luminogens (AIEgens), heterocycle-containing molecules are highly promising for this usage because of their high photostability and tunable electronic properties. In this work, a pyrazine-containing AIEgen wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To rule out the possibility of self-quenching of absorption of ABDA due to its simultaneous excitation upon exposure to radiation, we performed a blank experiment by exposing the solution of ABDA to light radiation for 20 minutes. No significant change in the absorption of ABDA was observed 25 (Fig. S20 in the Supplementary).…”
Section: Resultsmentioning
confidence: 95%
“…To rule out the possibility of self-quenching of absorption of ABDA due to its simultaneous excitation upon exposure to radiation, we performed a blank experiment by exposing the solution of ABDA to light radiation for 20 minutes. No significant change in the absorption of ABDA was observed 25 (Fig. S20 in the Supplementary).…”
Section: Resultsmentioning
confidence: 95%
“…Even thought he non-doped deviceb ased on these emitters was not fabricated,t he OLED employing theseA IE-active emitters exhibited decent performances with maximum EQE of 21.5 and 18.5 %f or TXO-PhCz and TXO-TPA, respectively.I n 2017, Tang et al reported another tailor-made luminogenic DBT-BZ-DMAC with strong AIE-TADF characteristics, as well as mechano-luminescence properties. [68] No close p-p stacking was found for BZ-DMAC fragments accordingt os ingle-crystal analysis; instead, the molecular structure was restricted by C-H-p hydrogen bonds. As ar esult,D BT-BZ-DMAC exhibits very small nonradiative dissipation in the aggregate state.…”
Section: Tadf Molecules With Aggregation Inducede Mission (Aie) Propementioning
confidence: 96%
“…In 2017, Tang et al. reported another tailor‐made luminogenic DBT‐BZ‐DMAC with strong AIE‐TADF characteristics, as well as mechano‐luminescence properties . No close π–π stacking was found for BZ‐DMAC fragments according to single‐crystal analysis; instead, the molecular structure was restricted by C—H—π hydrogen bonds.…”
Section: Tadf Molecular Design Towards Efficient Oleds With Superior mentioning
confidence: 99%
“…The two-photon cross-sections of the AIE photosensitizer dots were assessed by using two-photon imaging method in the wavelength range of 800 nm to 1040 nm at 20 nm intervals. [22] The value of two-photon cross-sections could improve to 7.36 × 10 5 GM for PTPEDC2 dots (17). Compared to TPEDC dots, PTPEDC2 dots show 548 % more efficient 1 O 2 generation efficiency and 651 % larger two-photon crosssection, which offered excellent 2PE-PDT performance in cancer cell ablation and zebrafish liver tumor treatment.…”
Section: Two-photon Aiegens Based On Tetraphenylethenementioning
confidence: 96%